The last hill : [large type] the epic story of a ranger battalion and the battle that defined WWII - Drury, Bob; Clavin, Tom, 1954- (Thorndike Press large print nonfiction series., 2022)
"In December 1944, Lt. Col. James Rudder's 2nd Battalion would form the spearhead into Germany. Rudder was given two objectives: Take Hill 400 and hold the hill 400 by any means necessary. Several Wehrmacht regiments had been given the exact same orders. The clash of the two forces was one of the bloodiest encounters of World War II. Of the 130 special operators who held the hill that December day, only 16 remained to stagger back down its frozen slopes. The Last Hill is a rich saga of what the survivors of the battalion would remember as "our longest day""--